GAD67機能不全によるマウス情動行動の変化 - 崎村, 建司; 中井, 淳一; 田中, 謙二; 糸原, 重美; 柳川, 右千夫; 藤原, 和之; 宮田, 茂雄; 柿崎, 利和; 大日方, 英; 平野, 瞳子; 阿部, 学; 渡辺, 雅彦; et al. (日本薬理学会年会要旨集, 2021)
Reduced expression of glutamate decarboxylase 67 (GAD67), encoded by Gad1 gene, is a consistent finding in postmortem brains of patients with schizophrenia, bipolar disorder and major depressive disorder. However, the neurobiological consequences of GAD67 dysfunction in mature brains are not fully understood because the homozygous Gad1 knockout is lethal in newborn mice. Here, we developed Gad1tTA/STOP-tetO biallelic knock-in mice using Gad1STOP-tetO and Gad1tTA knock-in mice, and compared them with Gad1+/+ mice. The expression level of GAD67 protein in brains of Gad1tTA/STOP-tetO mice treated with doxycycline (Dox) was decreased by approximately 90%. The GABA content was also decreased in the brains of Dox-treated Gad1tTA/STOP-tetO mice. In the open-field test, Dox-treated Gad1tTA/STOP-tetO mice exhibited hyper-locomotor activity and decreased duration spent in the center region. In addition, acoustic startle responses were impaired in Dox-treated Gad1tTA/STOP-tetO mice. These results suggest that global reduction in GAD67 elicits behavioral impairments in mice. These GAD67 knockdown mice will be useful for elucidating the neurobiological mechanisms of emotional abnormalities, such as anxiety symptoms associated with psychiatric disorders.